Laparoscopic surgery for colon cancer: quality requirements for (extended) right hemicolectomy - Lux, Philipp; Weber, K.; Hohenberger, Werner (Chirurg, 2014)
The current S3 guidelines on the surgical treatment of colorectal cancer note that with a suitable patient selection and expertise of the surgeon the same oncological results can be achieved laparoscopically as with the open procedure. This requires that the same quality requirements have to be provided for both methods. The most important quality parameters of right sided (extended) hemicolectomy are central ligation of the supplying arteries (ileocolic artery, right branch of the middle colic artery and middle colic artery) flush to the central origin of the vessel (superior mesenteric artery or middle colic artery) and the sharp dissection of the mesocolon without any preparation tears. The photographic documentation of the fresh surgical specimens for categorizing the preparation quality as well as to determine the pedicle of the vessel can capture this quality well and is also currently the best surrogate parameter to evaluate the oncological quality of the operation. At present, there are still considerable widespread deficits not only with the laparoscopic approach but also in open surgery which must be urgently fixed.
EVALuna2:15170